Effect of epitaxial growth rate on morphological, structural and optical properties of β-Ga2O3 films prepared by MOCVD. (May 2022) - Wang, Di; Ma, Xiaochen; Xiao, Hongdi; Chen, Rongrong; Le, Yong; Luan, Caina; Zhang, Biao; Ma, Jin
Highlights: β -Ga2 O3 films were grown on SrTiO3 (100) substrate by a high-vacuum MOCVD system. The β -Ga2 O3 film with a growth rate of 4.7 nmmin −1 is a monocrystalline film. The surface roughness and refractive index increase with the increase of the film growth rate. The transmittance of the Ga2 O3 samples in the visible region was around 75%. HRTEM proves that the film has high crystalline quality from the microscopic sale. Abstract: This study investigated the effects of growth rate on the properties of monoclinic β -Ga2 O3 films grown on SrTiO3 (100) substrates by Metal-organic Chemical Vapor Deposition. The β -Ga2 O3 films deposited at the low rate exhibited monocrystalline structure, for which the structural analyses identified the epitaxial relationship of β -Ga2 O3 (100) // SrTiO3 (100) with β -Ga2 O3 〈001〉 // SrTiO3 〈011〉. In the case of the same film thickness, as the growth rate increased from 2.1 to 10.1 nmmin −1, the surface root-mean-square roughness of the β -Ga2 O3 film increased from 6.96 to 8.41 nm, and the crystalline quality decreased obviously. The prepared β -Ga2 O3 films exhibited a band gap of about 4.9 eV, and the refractive index in 450–800 nm wavelength range was 2.25–2.02. Moreover, the transmittance of all samples in the visible region was around 75%. Graphical abstract: Image, graphical abstract